CommunityCORE: a case study and reflection on community development in rural, northeast Kansas - Allen, Ross M. (My University, 2015)
A local minister has purchased the building once used to house the Soldier High School gym prior to its closure in 1970. He is currently in the process of clearing the overgrown and garbage strewn grounds where the building sits and will then begin an effort to revitalize the building and refurbish the interior, converting it into a community development center. The intent of this internship was to join in his efforts and not only assist him in the physical renovation of the dilapidated building (a formidable task in and of itself) but also formalize an existing community alliance called Community CORE into a 501(c)(3) non-profit organization with a mission to revitalize the community that this center is meant to serve.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Allen, R. M. (2013). CommunityCORE a case study and reflection on community development in rural, northeast Kansas. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Community CORE Foundation; Rural development--Kansas--Soldier; Community development--Kansas--Soldier; Community centers--Kansas--Soldier; Reports; Reports